САМОСТІЙНА РОБОТА СТУДЕНТІВ З ФІЗИЧНОГО ВИХОВАННЯ (Педагогіка вищої та середньої школи, 2008)
The is a theoretical analyses of the researches of the sty dents’ tests problem on physical bringing up; there is the information of their own sociological research; the ways of solving the problems of the students tests on physical bringing up are shown.